Pengaruh Pemasaran Melalui Media Sosial Terhadap Niat Berbelanja pada Aplikasi Shopee - Heppy Anno Rey Pasaribu (Indonesia Marketing Association (IMA), 2022)
This research aims to determine the impact of digital marketing through social media on purchasing intentions on Shopee app. The data in this study is collected online from 185 Shopee users and social media using convenience sampling techniques and analyzed with the help of SmartPLS3 to empirically test the research model. The results show that there are four positive and significant relationship interactions among the study variables. This research can provide useful information related to digital marketing to practitioners related to digital marketing. The results of this study are expected to be used as considerations to make it easier for marketers to understand how ads perception, brand perception, and brand attitude can affect consumers' buying intentions in shopping on the Shopee app. , brand perception, brand attitude, buying intentions